Chinese ecocinema : in the age of environmental challenge - Lu, Sheldon H.; Mi, Jiayan (Hong Kong University Press ; Eurospan [distributor], 2009)
This anthology is a book-length study of China's ecosystem through the lens of cinema. Proposing 'ecocinema' as a new critical framework, the volume collectively investigates a wide range of urgent topics in today's world.